2022
DOI: 10.1186/s12884-022-04621-2
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable and non-modifiable risk factors for obstetric anal sphincter injury in a Norwegian Region: a case–control study

Abstract: Background Obstetric anal sphincter injury (OASI) is a common and severe complication of vaginal delivery and may have short- and long-term consequences, including anal incontinence, sexual dysfunction and reduced quality of life. The rate of OASI varies substantially between studies and national birth statistics, and a recent meta-analysis concluded that there is a need to identify unrecognized risk factors. Our aim was therefore to explore both potential modifiable and non-modifiable risk fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Santos et al 9 in their study with nulliparous women, determined that there was a significant relationship between the use of SynOT induction and perineal trauma. Similarly, Klokk et al 13 reported that augmentation with oxytocin is an independent risk factor for obstetric anal sphincter injury in primiparous and multiparous women. Despite these findings, Oliveira et al 7 in a retrospective study conducted in a public hospital, reported that no significant relationship exists between SynOT and spontaneous perineal lacerations.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Santos et al 9 in their study with nulliparous women, determined that there was a significant relationship between the use of SynOT induction and perineal trauma. Similarly, Klokk et al 13 reported that augmentation with oxytocin is an independent risk factor for obstetric anal sphincter injury in primiparous and multiparous women. Despite these findings, Oliveira et al 7 in a retrospective study conducted in a public hospital, reported that no significant relationship exists between SynOT and spontaneous perineal lacerations.…”
Section: Discussionmentioning
confidence: 93%
“…In the literature, there are different results of studies on the effects of oxytocin induction on the perineum 7,10,13 . Santos et al 9 in their study with nulliparous women, determined that there was a significant relationship between the use of SynOT induction and perineal trauma.…”
Section: Discussionmentioning
confidence: 99%
“…It should be emphasized that in the literature on the subject, there are numerous reports of spontaneous perineal trauma, in particular, severe perineal trauma. Perineal lacerations of the third and fourth degree are the most severe forms of spontaneous perineal trauma, and at the same time, are associated with numerous negative and long-term consequences for women's health [5,9,[13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%